Reading Interest to Millennial Students: Reading Self-Concept and Perceptions of Parental Involvement as Predictors - Tupen Ama, Roy Gustaf; Widyana, Rahma (Sains Humanika, 2021)
Purpose - this study aims to determine the relationship between self-concept of reading with reading interest in elementary school students; to determine the relationship between perceptions of parental involvement with reading interest in elementary school students; and to find out the relationship between self-concept of reading and perceptions of parental involvement in stimulants with reading interest. Methods - This research uses a correlational quantitative method. In this study, researchers used a scale, there are reading interest scale, the scale of self-concept reading, and the scale of perception of parental involvement. The sample in this study was 47 elementary school students. The sampling technique used purposive sampling with the characteristics of male and female students of elementary school, grades 3, 4 and 5, ages 8 to 11 years, living with parents and having good reading fluency. The analysis used is Pearson product moment correlation analysis and regression analysis. Findings - the results of the analysis show (1) There is a positive relationship between self-concept of reading with reading interest in students with a correlation coefficient (rxy) of 0.652 (p <0.01) with a contribution of 42.5%; (2) there is a positive relationship between the perception of parental involvement with reading interest in students with a correlation coefficient (rxy) of 0.697 (p <0.01) with a contribution of 48.6% and there is a relationship between the concept of self-reading and perception of parental involvement stimulants with interest in reading with a value of r = 0.690; F = 28,383; (p <0.01) with a contribution of 56.3% to interest in reading. The score of reading interest category is in the medium category with 83.00%, while the self-concept reading variable is in the high category with 59.70% and the perception variable of parental involvement is in the medium category with 93.00%. The findings of this study indicate that the importance of parental involvement and reading self-concepts in students increases student reading interest.